Old World, New Experiences: an Investigation of the Cognitive Complexity of Older Adults in an Online Dating Environment - (:unkn) unknown (My University, 2018)
This study seeks to add to the knowledge of cognitive complexity by examining its relationship with online dating amongst older adults in comparison to younger adults. Previous studies have indicated that individuals who score high in cognitive complexity produce better messages than those who don't. The majority of the studies about cognitive complexity and message production has centered around children, adolescents, and young adults. There has been no research addressing the cognitive complexity of elderly individuals in particular in an online dating setting. The present study addresses this gap by investigating the cognitive complexity of older adults involved in online dating in comparison to the cognitive complexity of younger adults. Data were collected from online dating profiles and the results showed that older individuals were more cognitively complex than younger adults. There was no significant difference between the cognitive complexity of older women in comparison to older men. The result of this study could help the understanding of individuals' cognition in a setting that is removed from the face-to-face environment. It could also help one's understanding of their cognitive complexity through utilizing the Role Category Questionnaire (RCQ) which is different from the original intent of the questionnaire - to measure the amount of construct in other people excluding one's self. This study increases our understanding of the display of cognitive complexity in an online dating environment amongst older adults and highlights how significantly different it is from the younger adults. Research and practice can benefit from more cognitive distinctions between age groups. Keywords: cognitive complexity, online dating, older adults dating.